Analisis Komparasi Tingkat Kesehatan Bank Syariah Indonesia dan Bank Central Asia Syariah dengan Metode RGEC - Nuriyah, Lailatun; Solihin, Khabib (JIOSE: Journal of Indonesian Sharia Economics, 2025)
This study analyzes the comparative performance of Bank Syariah Indonesia (BSI) and Bank BCA Syariah using financial ratios with the RGEC approach (Risk Profile, Good Corporate Governance, Rentability, and Capital), based on the Financial Services Authority (OJK) Regulation No. 08/POJK.03/2014. This research employs a quantitative method with a descriptive analysis approach. Secondary data were used, obtained from financial reports and GCG reports of Bank BSI and Bank BCA Syariah for the 2019–2022 period. The analysis results indicate growth in financial ratios and GCG for both banks, leading to an increase in their composite scores each year. Bank BSI achieved composite scores of 80%, 82%, 88%, and 88% over the last four years, while Bank BCA Syariah recorded scores of 71%, 73%, 77%, and 84% over the same period. The average composite score accumulation for Bank BSI was 84.5%, whereas Bank BCA Syariah achieved an average of 76.25%. Bank BSI was ranked at level 2 ("Healthy") in 2019–2020 and improved to level 1 ("Very Healthy") in 2021–2022. Meanwhile, Bank BCA Syariah consistently maintained a level 2 ("Healthy") ranking throughout the four-year period. Thus, the health level of Bank BSI was superior to that of Bank BCA Syariah during 2019–2022.